Paradoxes, problems and potentialities of online work platforms. (1st December 2017) - Nancy Ettlinger
Abstract : Drawing from a critical synthesis of interdisciplinary literatures, this article presents the organisational landscape of online work platforms as embedding problems posed to 'the crowd' while holding clues for paths of resistance. Organisational mechanisms that underpin online work platforms paradoxically both deterritorialise and territorialise online work and encompass new processes of disintermediation and intermediation, producing unprecedented savings for firms while imposing precarity on crowdworkers. Online work platforms nonetheless have become a tool of 'development' in underdeveloped countries for 'bottom-of-pyramid' (BOP) populations, a situation I critically examine regarding unique organisational features. Despite principles of online work platforms that would seem to foster the deterritorialisation of work, close scrutiny reveals spatially differentiated labour markets, which matter because the implications for change and the affordances of the new digital infrastructure differ across contexts.